KEMAMPUAN DAYA DUKUNG WISATA DAN KEPUASAN WISATAWAN DI NUSA LEMBONGAN - Istacahyani, Ida Ayu Modasih; Sunarta, I Nyoman; Sukewijaya, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 1 (2024), 2024)
This study investigates the tourism carrying capacity and factors influencing tourist satisfaction in Nusa Lembongan, emphasizing the importance of preserving its environmental quality. Using a mixed-methods approach with 110 respondents, the research identifies a daily carrying capacity of 12.044 visits, with observed visits in August surpassing the sustainable limit. The findings highlight the correlation between cleanliness, security, facilities, and attractions with heightened tourist satisfaction. Recommendations include addressing plastic waste concerns and fostering intergovernmental cooperation for sustainable tourism development. This study contributes valuable insights for preserving Nusa Lembongan's allure, emphasizing the delicate balance between tourism and environmental conservation to ensure prolonged visitor interest and satisfaction. Keywords: Tourism, Carrying, Capacity, Tourist, Satisfaction